2008
DOI: 10.1186/bf03352808
|View full text |Cite
|
Sign up to set email alerts
|

A new model of lunar crust: asymmetry in crustal composition and evolution

Abstract: Earlier models of lunar crustal formation as a simple flotation of ferroan anorthosites (FAN) do not account for the diverse crustal composition revealed by feldspathic lunar meteorites and granulites in the Apollo samples. Based on the integrated results of recent studies of lunar meteorites and global chemical and mineralogical maps, we propose a novel asymmetric crust model with a ferroan, noritic, nearside crust and a magnesian, troctolitic farside crust. Asymmetric crystallization of a primordial magma oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 49 publications
4
79
0
Order By: Relevance
“…Lunar anorthosites tend to be more magnesian in composition and bridge the gap between FAN and Mg-suite rocks (see also [34,48]). This is also true of the lunar meteorite plagioclase Eu-anomaly (figure 4), which bridges the gap between FANs and Mg-suite rocks.…”
Section: (B) Implications Of Heterogeneity In Crustal Anorthositesmentioning
confidence: 99%
“…Lunar anorthosites tend to be more magnesian in composition and bridge the gap between FAN and Mg-suite rocks (see also [34,48]). This is also true of the lunar meteorite plagioclase Eu-anomaly (figure 4), which bridges the gap between FANs and Mg-suite rocks.…”
Section: (B) Implications Of Heterogeneity In Crustal Anorthositesmentioning
confidence: 99%
“…Returned samples from the Apollo 12, 14 and 15 sites were found to contain highly elevated concentrations of incompatible trace elements, and these rocks were given the name KREEP, because of their high levels of potassium (K), rare earth elements (REE), and phosphorous (P). Although the absolute concentrations of these elements vary among the KREEP-rich samples, their relative concentrations tend to be roughly consistent (Warren and Wasson 1979;Arai et al 2008Arai et al , 2010.…”
Section: Lunar Tomography and Thorium Abundancementioning
confidence: 87%
“…Many researchers have suggested that a dichotomy in geological processes may have existed between the lunar nearside and farside (e.g., Warren and Wasson 1979;Arai et al 2008Arai et al , 2010Yamashita et al 2010, and many references therein). The two sides exhibit distinct differences in the surface topography (Araki et al 2009), gravity field (Namiki et al 2009;Yan et al 2012), crustal thickness (Hikida and Wieczorek 2007;Ishihara et al 2009;Wieczorek et al 2013), and composition (e.g., Arai et al 2008Arai et al , 2010.…”
Section: Lunar Tomography and Thorium Abundancementioning
confidence: 99%
See 2 more Smart Citations